1991
DOI: 10.4098/at.arch.91-5
|View full text |Cite
|
Sign up to set email alerts
|

Population and habitat characteristics of two sympatric species of Ctenomys (Rodentia: Octodontidae)

Abstract: . 1991. Population and habitat characteristics of two sympatric species of Ctenomys (Rodentia: Octodontidae). Acta theriol. 36: 87 -94.Demography, spatial distribution, body size and habitat characteristics of two sympatric species of Ctenomys have been studied seasonally at Necochea (Buenos Aires Province, Argentina). Densities were 11.3 individuals/ha for Ctenomys talarum and 5.2 indiv./ha for Ctenomys australis. Breeding was seasonal for both species. Sex ratios were unbalanced in favour of females in C. au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…At this locality, these species co‐occur in coastal habitats that are characterized by sandy soils and that are dominated by grasses and herbaceous plants. Although the study species occur in sympatry, they occupy slightly different habitats; although C. australis is restricted to sand dunes characterized by minimal vegetative cover, C. talarum inhabits more heavily vegetated inter‐dune areas and adjacent coastal grasslands (Malizia, Vassallo & Busch, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…At this locality, these species co‐occur in coastal habitats that are characterized by sandy soils and that are dominated by grasses and herbaceous plants. Although the study species occur in sympatry, they occupy slightly different habitats; although C. australis is restricted to sand dunes characterized by minimal vegetative cover, C. talarum inhabits more heavily vegetated inter‐dune areas and adjacent coastal grasslands (Malizia, Vassallo & Busch, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that, although most species of Ctenomys show disjunct distributions, the population here studied shares its geographic range with C. australis, constituting a rare case of sympatry (Contreras & Reig, 1965;Malizia, Vassallo & Busch, 1991).…”
Section: Introductionmentioning
confidence: 92%
“…Busch (1989) showed that C. australis thermoregulated better than C. talarum in cold and warm environments and also maintained a higher body temperature: limited thermoregulation occurred in C. talarum when it was colder than 20 8C but C. australis maintained body temperature down to 10 8C. It is therefore evident that the pattern of habitat segregation and soil utilization by the two species (Malizia et al, 1991;Comparatore et al, 1992) does not depend only on the morphological traits associated with digging. On the other hand, C. talarum and C. australis are very different in fur colour and body size.…”
Section: Integrating Morphological Physiological and Ecological Datamentioning
confidence: 98%
“…Figure 1 provides for both species a phylogenetic and geographical context. Previous work has shown the existence of a pattern of habitat segregation, according to soil and vegetation types, that characterizes the microspatial distribution of both species (Malizia, Vassallo & Busch, 1991;Comparatore, Agnudsdei & Busch, 1992). Previous work has shown the existence of a pattern of habitat segregation, according to soil and vegetation types, that characterizes the microspatial distribution of both species (Malizia, Vassallo & Busch, 1991;Comparatore, Agnudsdei & Busch, 1992).…”
Section: Introductionmentioning
confidence: 99%